2020
DOI: 10.1093/ajcp/aqaa193
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiologic, and Pathologic Characteristics of Pulmonary Hamartomas With Uncommon Presentation

Abstract: Objectives To investigate the clinicopathologic and radiologic features of pulmonary hamartomas (PHs) with uncommon clinical presentation. Methods A retrospective clinicopathologic and radiologic review was performed for patients diagnosed (1999-2019) with multiple hamartomas, lesions arising adjacent to a coexisting pulmonary malignancy, and tumors with predominantly extrapulmonary localization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…3 Although it can be seen in all age groups, most of them are detected in sixth or seventh decades of life. 4 Consistent with previous studies, the mean age was 53.0 ± 11.45 in our study. Previous studies suggested a 1.6-4 fold male predominance of pulmonary hamartoma.…”
Section: Discussionsupporting
confidence: 93%
“…3 Although it can be seen in all age groups, most of them are detected in sixth or seventh decades of life. 4 Consistent with previous studies, the mean age was 53.0 ± 11.45 in our study. Previous studies suggested a 1.6-4 fold male predominance of pulmonary hamartoma.…”
Section: Discussionsupporting
confidence: 93%
“…Endobronchial hamartomas account for only 1-19.5% of cases. 8 - 10 In our study, hamartomas were localized in the parenchyma in all cases, and no endobronchial localization was observed.…”
Section: Discussionmentioning
confidence: 39%
“…The main problem in asymptomatic patients is the difficulty in distinguishing pulmonary hamartoma from lung cancer. 10 , 11 In our series, 37.3% of the cases were asymptomatic in terms of the respiratory system, 27.1% of the cases had dyspnea, 23.7% had chest pain, and 20.3% had a cough. However, these findings are thought to be due to other possible pulmonary causes and not hamartoma.…”
Section: Discussionmentioning
confidence: 47%
“…PHs arise from the primitive mesenchymal tissue of the bronchial wall that can differentiate into variable mature mesenchymal tissues [ 12 ]. Cytogenetic analyses have revealed genetic aberrations of high mobility proteins, in chromosomal bands 6p21 or 12q14-15, or rarely in both bands, in PH patients [ 4 , 13 ]. In this regard, a specific translocation, t(6;14)(p21;q24), was detected in most PHs, leading to a partial fusion between the high mobility group AT-hook 1 (HMGA1) gene and RecA-like protein L (RAD51L), a gene encoding a protein kinase with a relevant role in the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a specific translocation, t(6;14)(p21;q24), was detected in most PHs, leading to a partial fusion between the high mobility group AT-hook 1 (HMGA1) gene and RecA-like protein L (RAD51L), a gene encoding a protein kinase with a relevant role in the repair process. Additionally, the rearrangement of 12q14-q15, involving the high mobility group AT-hook 2 (HMGA2) gene, can be detected in approximately 80% of patients [ 13 , 14 ]. Recent data are suggesting that there is an association between PHs and lung or other extrapulmonary neoplasms [ 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%